Prometno logistični terminal v Ljubljani - Čok, Gregor (Urbani izziv, 2001)
In Slovenia we have a vast legacy of so called industrial zones that were in the late planned economy placed and dimensioned for the needs of local industries. Most of them were spatially under utilised and modestly equipped with basic technical infrastructure. Considering their number and size of available surfaces the question is, whether it is sensible to burden new siteswith spatially wasteful contents. The article shows possibilities for using existing capacities for the development of the transport logistic terminal in Ljubljana. It presents the methodology for evaluating potential sites containing new economic and spatial locational criteria.
Keywords: industrija; Ljubljana; logistika; mestne četrti; mestni predeli; promet